Analysis of the Effectiveness of Teaching Factory (TEFA) Implementation in Vocational High Schools in Makassar City Based on the CIPP Evaluation Model - Dafrid Cahyadi Arifin; Wiwik Andriani; Nur Fadilah; Hermila A; Abdul Sakti (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
This study aimed to analyse the implementation of Teaching Factory, based on CIPP evaluation model (Context, Input, Process and Product) in Vocational High Schools in Makassar City. Methods This study carried out an evaluative research in the form of CIPP model (Contexts, inputs, processes and products). The research data were collected through observation, interview, documentation and questionnaire at SMKN 5 Makassar, SMKN 8 Makassar and SMK SMTI Makassar. The results discovered that the aspect context, enter, course of and product fell into the very good category. E. The context component suggested that the TEFA program is consistent with industrial needs and vocational education revitalization policies. The input component showed sufficient readiness of facilities, infrastructure, human resources and industrial support. The second, process component suggested that industry-standard practices of production- and service-based learning were effectively implemented. Results regarding the product component show that students developed higher competencies, work skills, and entrepreneurial attitudes. The study also identifies several of the main challenges, including limited available funding and unsuitable availability of production facilities at some schools. This paper provides recommendations for improving the quality of TEFA implementation through: (1) enhance facilities support, (2) develop technical implementation guidelines for TEFA, and (3) strengthen industrial partnerships in vocational schools.